Pengaruh Variasi Awal Data Pengamatan Terhadap Hasil Prediksi Pasang Surut Metode Admiralty (Studi Kasus Perairan Bengkalis) - Ramadhani Harahap; Andy Hendri; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Analysis of tidal components can be done with several methods, namely admiralty, semi graph, least square and so forth. Previous research indicates that the initial tidal data retrieval time has an effect on the result of tidal prediction. Tidal analysis method used in this research is admiralty method. Daily observation data of 15 days in each hour will be simulated against one hundred and fifty eight variations of time using Hijri calendar, to find out the initial variation of observational data that best matches the tidalprediction in bengkalis waters. The analysis results show that the smallest average RMSE value is on the initial variation of the 18th data for verification of the simulation data. The 18th days of the Hijri calendar is in the waning gibbous of moon phase, which is after the full moon phase. The tidal type of the location of the research based on the value of the Formzahl number entered in the classification of the double mixed tide prevailingtype (mixed tide prevailing semidiurnal).Keywords : tidal, method of Admiralty, Hijri calendar